2007
DOI: 10.1103/physrevb.76.054516
|View full text |Cite
|
Sign up to set email alerts
|

Tcsuppression and resistivity in cuprates with out of plane defects

Abstract: Recent experiments introducing controlled disorder into optimally doped cuprate superconductors by both electron irradiation and chemical substitution have found unusual behavior in the rate of suppression of the critical temperature Tc vs. increase in residual resistivity. We show here that the unexpected discovery that the rate of Tc suppression vs. resistivity is stronger for out-of-plane than for in-plane impurities may be explained by consistent calculation of both Tc and resistivity if the potential scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Second, "slow" and "fast" T c suppression cannot be determined by plotting T c vs. impurity concentration, but only vs. a scattering rate directly comparable to a theoretical scattering rate (see below), which is generally difficult to determine. The alternative is to plot T c vs. residual resistivity change ∆ρ, but a) this is only possible if the ρ(T ) curve shifts rigidly with disorder, and b) if comparisons with theory include a proper treatment of the transport rather than the quasiparticle lifetime [115]. Finally, the effect of a chemical substitution in a Fe-based superconductor is quite clearly not describable solely in terms of a potential scatterer, but the impurity may dope the system or cause other electronic structure changes which influence the pairing interaction.…”
Section: Multiband Bcs Theorymentioning
confidence: 99%
“…Second, "slow" and "fast" T c suppression cannot be determined by plotting T c vs. impurity concentration, but only vs. a scattering rate directly comparable to a theoretical scattering rate (see below), which is generally difficult to determine. The alternative is to plot T c vs. residual resistivity change ∆ρ, but a) this is only possible if the ρ(T ) curve shifts rigidly with disorder, and b) if comparisons with theory include a proper treatment of the transport rather than the quasiparticle lifetime [115]. Finally, the effect of a chemical substitution in a Fe-based superconductor is quite clearly not describable solely in terms of a potential scatterer, but the impurity may dope the system or cause other electronic structure changes which influence the pairing interaction.…”
Section: Multiband Bcs Theorymentioning
confidence: 99%
“…Such insensitivity to impurities is difficult to reconcile with a scenario of non-s-wave superconductivity. However, several established unconventional superconductors, such as organic 22 , cuprate 28 , pnictide 29 and heavy-fermion superconductors 30,31 , deviate from the Abrikosov-Gor'kov theory , with explanations ranging from spatial variation of the gap function 32 , the effect of a combination of magnetic and non magnetic impurities 33 , or interactions between paramagnetic impurities 34 . Hence, a definitive statement about the nature of the superconducting state will require further investigation, and in particular would benefit from the growth of single crystals and detailed studies of the gap symmetry.…”
Section: Superconductivitymentioning
confidence: 99%
“…Several authors attempted to account for the slowness of the T c suppression by assuming that the scattering potential of planar impurities was extended, or anisotropic [16,17,18,19]. Recently, Graser et al [20] calculated both T c and the impurity resistivity ρ within a consistent model of extended potential scatterers, and concluded that the unusual T c vs. ρ behavior seen in cuprate experiments should be attributed to strong correlations or strong coupling corrections to BCS theory. In general, the effect of correlations on the structure and scattering of quasiparticle states in a disordered d-wave superconductors is still an open and very important question for cuprates and other unconventional superconductors.…”
mentioning
confidence: 99%